Effectiveness Of Animated Video-Based Sexual Education On Sexual Knowledge Among Adolescents With Intellectual Disabilities: A Quasi-Experimental Study In Yogyakarta, Indonesia - Masta Hutasoit (Journal of health research and technology, 2026)
Adolescents with disabilities have limitations in intellectual abilities, thinking, and adaptive skills, so they need special support in the learning process, including in understanding sexual education. Low knowledge about sexuality makes disabled adolescents vulnerable to inappropriate behavior and the risk of sexual abuse. This study aims to determine the effect of the use of animated video media on sexual education knowledge in adolescents with disabilities at SLB Negeri Pembina Yogyakarta. This study uses a quantitative method with a pre-experimental design of one-group pre-test and post-test. The research sample amounted to 43 respondents who were selected using the total sampling technique. The research instrument was in the form of a sexual education knowledge questionnaire that had been tested for validity (r count > r table = 0.361) and reliability (Cronbach's Alpha = 0.952). Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed that before being given an intervention, most of the respondents had a level of knowledge in the poor category (69.8%), while after being given an animated video increased to good (48.8%) and very good (30.2%). The results of the Wilcoxon test showed p = 0.001 (p < 0.05), indicating a significant difference between before and after the intervention. Based on the results of research and data analysis, it can be concluded that animated video media has a significant effect on improving the sexual knowledge of disabled adolescents, so that it can be used as an effective and interesting educational media in special schools.